2012
DOI: 10.1007/s13762-012-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of bisphenol A on lignin: effects of solution chemistry

Abstract: Adsorption of bisphenol A on a lignin isolated from black liquor, a waste product of the paper industry, was investigated to assess the possibility of using the lignin to remove bisphenol A from waters. Effects of pH, ionic strength, heavy metals, and dissolved organic matter (DOM) on adsorption were examined. Adsorption equilibrium was approached within 5 h. The adsorption capacity of bisphenol A on lignin was as high as 237.07 mg/g. Ionic strength had no influence on the adsorption, while higher pH above 7.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Specifically, the work demonstrated that these modified carbons prepared using high-temperature steam or methane/steam offered better behavior than conventional activated carbons. However, there are few works available focusing on the BPA removal from water when other types of contaminants are also present in the water [36][37][38][39]. BPA is a high-volume industrial chemical used in the production of epoxy resins and polycarbonate plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the work demonstrated that these modified carbons prepared using high-temperature steam or methane/steam offered better behavior than conventional activated carbons. However, there are few works available focusing on the BPA removal from water when other types of contaminants are also present in the water [36][37][38][39]. BPA is a high-volume industrial chemical used in the production of epoxy resins and polycarbonate plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of pH on BPA adsorption, uneven results have already been reported in the literature. 8,9,59 In this study, it can be seen that electrostatic interactions do not affect the adsorption of BPA on this adsorbent since the pH ZPC of ACS75 was 4.6, as listed in Table 3. Although BPA carries two hydroxyl groups, at neutral pH it takes on a molecular form but it undergoes protonation in an acidic medium and deprotonation in a basic medium (pH > 7).…”
Section: Effect Of Ph and Adsorption Mechanismmentioning
confidence: 75%
“…4 BPA is a highly toxic substance: it possesses carcinogenic and mutagenic activity and it can accumulate in the human body through the food chain causing dysfunction of the reproductive organs and, hence, poses a major security threat to the safety and health of all living organisms. 4,[8][9][10] That is why there is an urgent need to develop simple, easy, and efficient methods to remove BPA from the environment. 5,7 For this purpose, several water-treatment methods have been developed for the elimination of BPA.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, increased interest is focused on lignin as an adsorbent alternative to other wastewater treatments. Lignin, the second most abundant and the most complex polymer in nature (Agarwal et al, 2018), is known to exhibit adsorption properties and has been used for the efficient removal of heavy metals and organic contaminants such as dyes, bile acid, surfactants, pesticides, phenols, and polycyclic aromatic hydrocarbons from aquatic environments (Han et al, 2012). Specifically, some adsorbents prepared from lignin have attracted considerable interest.…”
Section: Introductionmentioning
confidence: 99%